PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERORIENTASI SAINS TEKNOLOGI MASYARAKAT DISERTAI PETA KONSEP PADA MATERI BIOTEKNOLOGI - Efdillah, Syilvia; Lufri, Lufri; Ahda, Yuni (Kolaboratif, 2013)
Biology is a subject directly related to everyday life and requires an understanding of the concept. Therefore, the learning process requires a biological approaches, strategies, methods, and media-related learning with the real world so that students can understand the concepts and learning becomes more meaningful. One of the learning strategies that can help the understanding of the concept as well as activities to direct and stimulate students' thinking is through the use of learning modules accompanied concept map. The aims of this research is to develop a module oriented science technology society on the topic of biotechnology. This Biology Module developed using 4-D models. The results shows that, the modules are very valid with a value of 81.09%. The value of practicalities by teachers are 82.7%, and the value of practicalities by students are 85.5%. The effectiveness of the module can be seen from the motivation of students, activities, and student learning outcomes. It is concluded that the biology module oriented science technology society (STS) accompanied concept map on the topic of biotechnology for junior high school was valid, practical, and effective.